The theatre of Rupert Goold : radical approaches to adaptation and new writing - Grochala, Sarah (Methuen Drama, 2021)
"Since the late 1990s, Rupert Goold has garnered a reputation as one of the UK's most exciting and provocative theatre directors. His exhilarating, risk-taking productions of both classic texts and new plays have travelled from regional stages to the National Theatre, the West End, Broadway and beyond. Through his artistic directorship of Headlong and then London's Almeida theatre, he has radically transformed, not only the companies themselves, but the landscape of British theatre. This is the first book to survey and analyse the full range of Goold's work and is a vital resource for students, scholars and his fans on different continents. The Theatre of Rupert Goold offers a backstage view of both Goold's work and the work of other major UK theatre artists he has nurtured, including Robert Icke, Blanche McIntyre, Mike Bartlett and Lucy Prebble. It gives an inside view of the processes behind some of Goold's most successful productions and explores in detail Goold's approach to making work that asks provocative questions of the modern world in the most theatrical ways imaginable. The book features detailed analyses of key productions including Six Characters in Search of an Author, ENRON and 1984 for Headlong, besides productions of Macbeth (Chichester Festival Theatre; Gielgud Theatre, London; BAM; Lyceum Theater Broadway), Time and the Conways (National Theatre) and The Merchant of Venice (RSC) and his move into screen with Macbeth (BBC) and The Hollow Crown (BBC). Together with insights from the playwrights, directors, actors and designers who have collaborated with Goold, it provides an accessible and fascinating guide to Goold's approach to making theatre, placing his work within the wider context of contemporary performance"--